Study on the Influence of Cinnamon Powder on the Corrosion Resistance of 21K Gold Alloy in Artificial Saliva in the Presence of Cinnamon Powder (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Corrosion resistance is a critical factor influencing the long-term performance and biocompatibility of dental and biomedical alloys. This study explores the corrosion behaviour of 21K gold alloy and other metallic materials in artificial saliva both in the presence and absence of cinnamon powder. Cinnamon, a common natural flavouring agent used in food and oral care products contains bioactive compounds that may alter the electrochemical environment of the oral cavity. Corrosion testing was performed using potentiodynamic polarisation and electrochemical impedance spectroscopy (EIS) to evaluate the electrochemical stability of the materials. The results indicated that the presence of cinnamon powder enhances the corrosion resistance of 21K gold alloy. These findings suggest that the dietary or therapeutic use of cinnamon powder could influence the durability and performance of metallic dental and orthodontic devices.